Extensive disseminated cysticercosis with involvement of all possible rare sites in a single patient – MRI and USG diagnosis - Amarjit Kaur; Naveen Pawar; Jaswinder Kaur Mohi; Simmi Bhatnagar; Shivani Sharma; Rajiv Bhalla (International Journal of Medical Research and Review, 2016)
Cysticercosis due to its extensive study is known to be one of the common tropical diseases. The spectrum of the disease extension and involvement has been updated continuously and every time case reports have come with new conclusions as the disease is seen worldwide. Disseminated cysticercosis by itself is a rare complication of cysticercosis with involvement of skeletal, ocular and tongue muscles. Pulmonary and cardiac involvements are rare and there are hardly few cases worldwide. Surprisingly we could identify such tiny cysticerci in the lung parenchyma, cardia and thyroid apart from other known dissemination sites .Isolated pulmonary cysticercosis have been reported but simultaneous involvement of other unusual sites is a rarity. Most of diagnosis in our case is by MRI and some by USG.Hence we report MR and USG imaging of such a case of disseminated cysticercosis involving all the possible rare sites in a single young Indian male patient who presented with history of seizures. This documentation and reporting will add up to the few cases reported previously, some of which are in isolation.